Petani Versus Penguasa: Perampasan Tanah Dan Perlawanan Petani - Syafnil (Universitas Katolik Parahyangan, 2022)
Economic improvement through foreign investment in the plantation sector, for example, increasing capitalization and plantation expansion continues to erode customary land. Customary land encroachment is an issue that often sticks to the expansion of oil palm plantations. An unfavorable mechanism for resolving land conflicts led to prolonged resistance between the Peasants and the rulers. This research uses qualitative methods with ethnographic studies, with critical analysis. Data collection techniques through interviews, participatory observation, literature studies, and documentation support data obtained from the field. The selection of informants uses snowball sampling. The case in Nagari Lingkuang Aua is viewed from the point of view of ecological politics and Peasant Resistance. Research findings show that land conflicts between farmers and companies have been occurring for a long time. The demands of the crate society were not taken seriously by the company. the company is stalling for time by taking refuge behind the HGU permits they have. Such conditions are also supported by the weak critical reasoning of local governments. They tend to protect the company and not investigate further because the company already has an HGU. The disillusionment of the farming community made them continue their resistance until now.